DISPARITY OF PUNISHMENT AT THE COURT OF THE CRIME OF CORRUPTION - -, Arifuddin; -, Aswanto; Akub, Sukti; Heryani, Wiwie (Journal of Humanity, 2015)
Research on the judges ruling against the disparity of offender criminal acts of corruption as well as the factors that influence the occurrence of the judges verdict, the disparity was held in the Court of a criminal offence, Corruption in the courts, the courts of Makassar Tipikor Tipikor Bandung, with this type of problem identification research perskriptif-shaped, with the descriptive nature of the use of legal normative approach. Primary data obtained through interviews with as many as 15 judges and prosecutors as well as 7 5 academics 3 advocates determination technique done with a sample of secondary data and sampling purporsiv acquired through the study of librarianship is analyzed then qualitatively.The research results showed that determination of the disparity, mistakes and condemnation to the perpetrator of the criminal offence of corruption in the courts, the courts of Makassar Tipikor Ti [ikor Jakarta and Bandung Tipikor Court as well as in the great Mahkama occurs because positive Indonesia corruption criminal law that gives broad freedom to determine fault and criminal type (strafsoort) both weighs criminal ringannya or (strafmaat) to the perpetrator of the criminal offence of corruption all not under the minimum standard of judgment and memlampaui the maximum punishment standards defined in legislation the eradication of criminal acts of corruption. Factors that cause the occurrence of an error or judgment determining the disparity to the perpetrator of the criminal offence of corruption in the courts, the courts of Makassar Tipikor Ti [ikor Jakarta and Bandung Tipikor Court as well as in legal substance Agungadalah Mahkama factor, which gives freedom to the judge in deciding guilt and punishment inflicted to the defendant, politics and power, because the perpetrator of the criminal offence of corruption involves many officials or former officials of the regional social stratification, which is strong in the Association community city of Makassar, which puts an official or former official as a person who has a high degree of social stratification, and the judge in the determination of fault to the defendant, as well as the reasons pemberatan and relaxation of his judgement very subjective judgment by the Tribunal judges